Initial experience with orbital atherectomy in a tertiary centre in the Netherlands - den Dekker, Wijnand K.; Siskos, Anastasios-Alexandros; Wilschut, Jeroen M.; Nuis, Rutger-Jan; Scarparo, Paola; Neleman, Tara; Masdjedi, Kaneshka; Ligthart, Jurgen M. R.; Diletti, Roberto; Daemen, Joost; Van Mieghem, Nicolas M. (Netherlands Heart Journal, 2023)
In January 2021, the Diamondback 360 orbital atherectomy (OA) system received CE mark approval and became available in Europe. The first procedure in Europe was performed at the Thoraxcenter, Erasmus Medical Center, Rotterdam, the Netherlands.